Analysis of the Role of Individuals and Governments in Post-COVID-19 Health Issues: The Case of Korea - Choi , Young-Chool (EAI Endorsed Transactions on Pervasive Health and Technology, 2022)
This study was conducted in order to ascertain what role government and individuals should play in the event of a pandemic such as Coronavirus occurring in Korea in the future, using information deriving from news articles available at the Bigkinds news portal site in Korea. The analysis period ran from 11 March 2020, when the pandemic was declared by the World Health Organization, to 31 January 2023, almost three years later. Text mining analysis was conducted on all the articles, as a result of which six important roles that individuals should play, and ten roles that government should play, in a pandemic situation were suggested.
Keywords: Pandemic; Text mining analysis; Role of individuals and government